Pre‐contrast CT attenuation of the thyroid gland is lower in brachycephalic dogs versus non‐brachycephalic dogs. Issue 1 (2nd November 2020) - Amorós, Olga; Espada, Yvonne; Vila, Anna; Jiménez, Alejandro; Novellas, Rosa
Abstract: Computed tomography has been used in human medicine to evaluate the thyroid gland functional status by means of Hounsfield units (HU). Studies describing attenuation value abnormalities, other than those in thyroid neoplasia, lack in veterinary medicine. The authors have observed a subjective reduction in thyroid attenuation in some patients undergoing CT for reasons other than thyroid disease. This finding has been identified more frequently in brachycephalic breeds compared to non‐brachycephalic breeds. In order to determine the thyroid gland attenuation variability on CT, a retrospective and prospective, analytical, cross‐sectional study was performed. The thyroid attenuation values of 65 client‐owned dogs were assessed using a 16‐slice helical CT scanner. Differences in attenuation between brachycephalic and non‐brachycephalic dogs were estimated by Welch's t ‐test. Serum TT4 and TSH levels were available in 26 patients. Statistically significant differences were observed in the pre‐contrast attenuation value ranges between brachycephalic and non‐brachycephalic dogs ( P  = .04). The pre‐contrast attenuation value range for the brachycephalic group was 69.1‐108 HU while being 75.8‐121 HU for the non‐brachycephalic group. No significant correlation was found between thyroid attenuation and serum thyroid hormone levels in our population ( P  > .6). All patients with hypoattenuating thyroid were brachycephalic and reported euthyroid. In conclusion, brachycephalic dogs seem to have a pre‐contrast attenuation thyroid gland range lower than non‐brachycephalic dogs. The present study contributes to the veterinary literature by providing a new thyroid attenuation value range for brachycephalic breeds. Additionally, hypoattenuating thyroid glands may be found in dogs with normal TT4 and TSH values.